1998
DOI: 10.1016/s0886-3350(98)80287-3
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of surgically induced astigmatism after sutureless temporal clear corneal and scleral frown incisions

Abstract: Corneal stability was achieved with minimal astigmatic change 1 week after scleral frown incisions, while clear corneal incisions induced greater WTR astigmatism with delayed stabilization 1 to 3 months postoperatively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0
3

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 18 publications
1
15
0
3
Order By: Relevance
“…These cases are included in the overall analysis because previous work has shown these scleral incisions to be astigmatically neutral. 41,42 All eyes had 1 relaxing incision placed in each steep hemimeridian (2 incisions/eye). The length of each incision ranged from 35-to 90-with a combined total incision length ranging from 95-to 160-.…”
Section: Methodsmentioning
confidence: 99%
“…These cases are included in the overall analysis because previous work has shown these scleral incisions to be astigmatically neutral. 41,42 All eyes had 1 relaxing incision placed in each steep hemimeridian (2 incisions/eye). The length of each incision ranged from 35-to 90-with a combined total incision length ranging from 95-to 160-.…”
Section: Methodsmentioning
confidence: 99%
“…12,14,24 Rao et al reported on the method of enlarging the size of the standard temporal clear corneal incision to reduce pre-existing ATR astigmatism of more than 1.75 D. 25 In our study, the degree of pre-existing astigmatism ranged from 0 D to 2.2 D. A small SIA with a trend toward a WTR axis shift was noted in both incision groups during the postoperative 12-weeks observation period (Tables 5 and 6). We found a more predictable reduction in pre-existing ATR astigmatism in the 2.5 mm incision group, but not in the 3.5 mm incision group (Tables 5 and 6).…”
Section: Discussionmentioning
confidence: 52%
“…[3] To avoid an effect on corneal refraction, the appropriate size of corneal incision for self sealing is 3.0-3.5 mm in width and 1.7-2.0 mm in length. In our study, all operations were performed by the same surgeon who is right handed.…”
Section: Discussionmentioning
confidence: 99%